Diagnostic Utility of Neutrophil-to-Lymphocyte Ratio in Correlation with Procalcitonin Levels among Neonates with Suspected Sepsis - Nurhidayanti, Nurhidayanti; Aristoteles, Aristoteles (Medical Laboratory Technology Journal, 2025)
Neonatal sepsis remains a significant cause of morbidity and mortality globally, particularly in resource-limited settings. The gold standard blood culture is limited by delayed turnaround time and suboptimal sensitivity, necessitating rapid, reliable biomarkers such as the neutrophil-to-lymphocyte ratio (NLR) and procalcitonin (PCT). Objective: to investigate the correlation between NLR and PCT levels in neonates with suspected sepsis, and evaluate the feasibility of NLR as an early diagnostic tool alongside PCT. A cross-sectional study was conducted at Muhammadiyah Hospital, Palembang, Indonesia, from January to March 2024. Thirty neonates aged 0–28 days with clinical suspicion of sepsis were recruited by purposive sampling. NLR values were obtained from automated hematology analyzers, and PCT levels were measured using fluorescence immunoassay. Statistical analysis used Spearman’s correlation, with p < 0.05 considered significant. The mean NLR was 3.99 (range: 2.3–6.2), and the mean PCT level was 5.72 ng/mL (range: 2.9–9.2 ng/mL). A significant positive correlation was observed between NLR and PCT (r = 0.684, p < 0.001), indicating that higher NLR values corresponded with elevated PCT levels. The study concludes that NLR shows a strong, statistically significant correlation with PCT in neonates with suspected sepsis. As a cost-effective and widely available marker, NLR can serve as an early screening tool, with PCT providing confirmatory value. However, the findings should be interpreted with caution due to the small sample size and single-center study design, which may limit the generalizability of the results.